Oxidation of sulfides in aqueous media catalyzed by pyrazole-oxidoperoxido-molybdenum(VI) complexes - Bruno, Sofia M. (2022)
The complex [MoO(O2)2(pyrazole)2] (1) is an effective catalyst for the oxidation of organic sulfides (methylphenylsulfide and diphenylsulfide). Reactions can be run in water as the only medium, at low temperature (25 °C), with low catalyst loadings (0.2 mol%) and excellent H2O2 efficiency with no significant non-productive decomposition of the oxidant. Under conditions that favor sulfone formation, the overall process, including isolation of the precipitated product (by filtration or centrifugation) and recycling of the aqueous phase containing the catalyst, can be performed in the absence of organic or ionic liquid solvents. Catalytic results with the recycled aqueous phase were the same as those obtained in the first cycle. With water as the sole solvent, 1 is a superior catalyst to the 3,5-dimethylpyrazole complexes [MoO(O2)2(dmpz)2] (2) and [Hdmpz]4[Mo8O25.8(O2)0.2(dmpz)2]·4H2O (3). Crystal structures for 1 and 3 are presented.